ANALISIS KEPUTUSAN PEMBELIAN HANDPHONE PADA KELOMPOK KONSUMEN DRIVER OJEK ONLINE - Rezza Dwi Santoso, (2020)
This study discusses the decision to purchase mobile phones on online motorcycle taxi driver consumer groups. This research is a quantitative study that aims to study the effect of promotion, product attributes and prices on cell phone purchasing decisions on online motorcycle taxi driver groups. The population of this study is mobile users in the online motorcycle taxi drivers in the Greater Jakarta area. The number of samples taken was 100 respondents with non-probability sampling method with the type of purposive sampling. Data collection is done through questionnaire collection. The data analysis technique used is descriptive analysis and inferential analysis, using the Partial Least Square (PLS) tool. The results of this study indicate that promotion variables, product attributes and prices are significant for purchasing decisions. Keywords: Handphone, Promotion, Product Attributes, Price and Purchasing Decisions